Audit Komunikasi Proklim: Langkah Hijau PT Kilang Pertamina Internasional RU III Plaju - Beni Iqbal; Adli Adli; Dendi Dendi (Sadida Islamic Communications and Media Studies, 2026)
This study presents a communication audit of the Climate Village Program (PROKLIM) implemented by PT Kilang Pertamina Internasional RU III Plaju Sumbagsel as part of its Corporate Social Responsibility (CSR) initiative. This research using a qualitative descriptive approach with in-depth interviews, field observation, and document analysis, this research evaluates communication effectiveness across five stages: problem identification, diagnosis, planning and implementation, recommendations, and evaluation. Findings reveal that ongoing socialization and education strategies have successfully increased community awareness and participation in climate mitigation activities such as tree planting and waste management. However, the study identifies significant gaps in transparency, community participation in communication planning, and the accessibility of program information. The communication monitoring system was perceived as insufficiently open and participatory. This audit recommends restructuring communication channels to be more adaptive, inclusive, participatory, and dialogic, to ensure PROKLIM becomes a genuinely community-driven movement that produces sustainable social and environmental impacts.